Localization of ATP-sensitive K(+) channel subunits in rat liver - Zhou, Ming (World J Exp Med, 2019)
BACKGROUND: ATP-sensitive K(+) (K(ATP)) channels were originally found in cardiac myocytes by Noma in 1983. K(ATP) channels were formed by potassium ion-passing pore-forming subunits (Kir6.1, Kir6.2) and regulatory subunits SUR1, SU2A and SUR2B. A number of cells and tissues have been revealed to contain these channels including hepatocytes, but detailed localization of these subunits in different types of liver cells was still uncertain. AIM: To investigate the expression of K(ATP) channel subunits in rat liver and their localization in different cells of the liver. METHODS: Rabbit anti-rat SUR1 peptide antibody was raised and purified by antigen immunoaffinity column chromatography. Four of Sprague-Dawley rats were used for liver protein extraction for immunoblot analysis, seven of them were used for immunohistochemistry both for the ABC method and immunofluorescence staining. Four of Wistar rats were used for the isolation of hepatic stellate cells (HSCs) and Kupffer cells for both primary culture and immunocytochemistry. RESULTS: Immunoblot analysis showed that the five kinds of K(ATP) channel subunits, i.e. Kir6.1, Kir6.2, SUR1, SUR2A, and SUR2B, were detected in liver. Immunohistochemical staining showed that Kir6.1 and Kir6.2 were weakly to moderately expressed in parenchymal cells and sinusoidal lining cells, while SUR1, SUR2A, and SUR2B were mainly localized to sinusoidal lining cells, such as HSCs, Kupffer cells, and sinusoidal endothelial cells. Immunoreactivity for SUR2A and SUR2B was expressed in the hepatocyte membrane. Double immunofluorescence staining further showed that the pore-forming subunits Kir6.1 and/or Kir6.2 colocalized with GFAP in rat liver sections and primary cultured HSCs. These K(ATP) channel subunits also colocalized with CD68 in liver sections and primary cultured Kupffer cells. The SUR subunits colocalized with GFAP in liver sections and colocalized with CD68 both in liver sections and primary cultured Kupffer cells. In addition, five K(ATP) channel subunits colocalized with SE-1 in sinusoidal endothelial cells. CONCLUSION: Observations from the present study indicated that K(ATP) channel subunits expressed in rat liver and the diversity of K(ATP) channel subunit composition might form different types of K(ATP) channels. This is applicable to hepatocytes, HSCs, various types of Kupffer cells and sinusoidal endothelial cells.